Clostridioides difficile strain-dependent and strain-independent adaptations to a microaerobic environment. Issue 12 (15th December 2021) - Weiss, Andy; Lopez, Christopher A.; Beavers, William N.; Rodriguez, Jhoana; Skaar, Eric P.
Abstract : Clostridioides difficile (formerly Clostridium difficile ) colonizes the gastrointestinal tract following disruption of the microbiota and can initiate a spectrum of clinical manifestations ranging from asymptomatic to life-threatening colitis. Following antibiotic treatment, luminal oxygen concentrations increase, exposing gut microbes to potentially toxic reactive oxygen species. Though typically regarded as a strict anaerobe, C. difficile can grow at low oxygen concentrations. How this bacterium adapts to a microaerobic environment and whether those responses to oxygen are conserved amongst strains is not entirely understood. Here, two C. difficile strains (630 and CD196) were cultured in 1.5% oxygen and the transcriptional response to long-term oxygen exposure was evaluated via RNA-sequencing. During growth in a microaerobic environment, several genes predicted to protect against oxidative stress were upregulated, including those for rubrerythrins and rubredoxins. Transcription of genes involved in metal homeostasis was also positively correlated with increased oxygen levels and these genes were amongst the most differentially transcribed. To directly compare the transcriptional landscape between C. difficile strains, a 'consensus-genome' was generated. On the basis of the identified conserved genes, basal transcriptional differences as well as variations in the response to oxygen were evaluated. While several responses were similar between the strains, there were significant differences in the abundance of transcripts involved in amino acid and carbohydrate metabolism. Furthermore, intracellular metal concentrations significantly varied both in an oxygen-dependent and oxygen-independent manner. Overall, these results indicate that C. difficile adapts to grow in a low oxygen environment through transcriptional changes, though the specific strategy employed varies between strains.